Guest

If the roots of the equation (a-b) x 2 + (b-c) x + (c-a) = 0 are equal , then prove that 2a = b + c .

If the roots of the equation  (a-b) x2 + (b-c) x + (c-a) = 0  are 
equal , then prove that  2a = b + c .

Grade:11

1 Answers

Arun
25758 Points
3 years ago
Dear student
 
As we see that x = 1 satisfy this
Hence both roots are 1.
 
Hence
Product of roots = 1 = c-a /a-b
 
a-b = c -a 
 
2a = b +c

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free